1986
DOI: 10.1210/jcem-63-3-709
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone (GH) Provocative Testing Frequently Does Not Reflect Endogenous GH Secretion*

Abstract: GH secretion was studied in 73 children with classical GH deficiency or GH neurosecretory dysfunction (GHND), intrinsic short stature, or normal stature. The GH-deficient group was defined by a peak GH secretory response below 10 ng/ml to all provocative tests (arginine, L-dopa, insulin hypoglycemia, and clonidine). GHND was defined by a mean serum 24-h GH concentration below 3 ng/ml, with a normal response (greater than or equal to 10 ng/ml) to provocative testing. Twenty-one GH-deficient children, 21 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
85
1
8

Year Published

1987
1987
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(100 citation statements)
references
References 26 publications
6
85
1
8
Order By: Relevance
“…It has been suggested that some children with idiopathic short stature (ISS), including familial short stature and/or constitutional delay, may have a low spontaneous GH secretion in contrast to normal serum GH responses to provocative testing, a condition called 'GH neurosecretory dysfunction' (Bercu et al, 1986;Spiliotis et al, 1984). Although this term cannot be clearly defined, even less adequately than the term G H deficiency (GHD), GH secretion certainly varies among the children with ISS and it is suggested that some of these children may produce less G H than they need for adequate growth (AlbertssonWikland & Rosberg, 1988;Zadik et al, 1992a).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that some children with idiopathic short stature (ISS), including familial short stature and/or constitutional delay, may have a low spontaneous GH secretion in contrast to normal serum GH responses to provocative testing, a condition called 'GH neurosecretory dysfunction' (Bercu et al, 1986;Spiliotis et al, 1984). Although this term cannot be clearly defined, even less adequately than the term G H deficiency (GHD), GH secretion certainly varies among the children with ISS and it is suggested that some of these children may produce less G H than they need for adequate growth (AlbertssonWikland & Rosberg, 1988;Zadik et al, 1992a).…”
Section: Discussionmentioning
confidence: 99%
“…However, this should be partly compensated for by the design of this study with age-and sex-matched healthy controls. The evaluation of 12 or 24 h GH profiles has been suggested to be superior to stimulation tests (37,38), but this is still controversial (39).…”
Section: Cf-ngt Cf-dm Cf-ngt and Cf-dmmentioning
confidence: 99%
“…Because blood IGF-1 reveals overall GH secretion during the period of prior 24 hrs and minimally fluctuates over this period [5][6][7], its concentration has been a reliable indicator of GH secretion [1,3,8]. Thus, the recent criteria for surgical cure of acromegaly mandate normalization of IGF-1.…”
mentioning
confidence: 99%